the Gender-based differences in AI usage and their impact on digital competency acquisition among Islamic teachers in Southern Pakistan: english - Majeed, Muhammad Kashif; Ahmad, Tunku Badariah Binti (International Journal of Nusantara Islam, 2025)
The study looks at how men and women in Southern Pakistan teaching Islamic subjects use AI tools and what impact this has on their digital competencies. Now that AI is used in schools, knowing how gender affects people’s ability to use these tools is necessary for ensuring that digital transformation in religious education is inclusive. There are three main objectives that drove the study. There are three main objectives: to study how AI is influenced by gender among Islamic teachers; to evaluate whether men or women are more skilled in digital use in Islamic education; and to find out whether digital talent rises as a result of using AI in teaching contexts. A survey device, used in conjunction with a quantitative research method, was deployed to collect information from 150 male and 150 female Islamic teachers. Gender differences were studied using descriptive statistics and independent sample t-tests, while multiple regression was carried out to determine if AI use played a role in increasing digital skills. The survey results indicated that males use AI more than females and that the reverse is true for digital tasks. In addition, using AI tools was shown to strongly influence digital competency development in both populations, indicating that this usage can help with greater improvements in digital skills. These results suggest ways in which policymakers, curriculum designers, and educational leaders can enhance digital literacy in religious education, especially among people from disadvantaged areas.